University students’ abstract reasoning level - Luis Vilchez, Jose; Orellana Palacios, Lic. Carlos Esteban (Transformación, 2021)
Objective: The academic performance influences academic desertion. The literature points out several factors of cognitive development that determine everyday life achievements, particularly in academic life. This paper aims at exploring academic reasoning levels at a sample of university students. Methods: The author relies on an abstract reasoning test and a quasi-experimental analysis given to 571 students of nine areas of knowledge at the University of Cuenca, Ecuador, who agreed to take part in the study.Results: No significant differences were found between levels of abstract reasoning between students of different knowledge areas. The most outstanding finding was that 68.5% of the sample would not pass the abstract reasoning exam.Conclusion: These findings show that on the basis of the relationship between abstract reasoning and academic performance highlighted in the specialized literature, it since recommendable to reinforce the development of abstract reasoning in initial stages of institutionalized Education.
Keywords: Abstract reasoning; academic achievement; academic standards; university students